Autopsy Based Prospective Study of Synthetic Cow Dung Poisoning (Yellow Sani Powder Poisoning) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Traditionally it is believed that cow dung has germicidal and insect repellent properties in the Indian Sub Continent.South Indian people have been using the natural cow dung for cleaning, lining and painting the courtyard andhouse premises. In this modern era, owing to the unavailability of natural cow dung, the people have resorted tousing synthetic dye (synthetic cow dung) which is called colloquially as “Manjal Sani Powder” in Tamil. Syntheticcow dung powder(Auramine) - a dye compound, even though legally banned, is till date easily available locallywith small shops and vendors. Aim of the present study is to explore the postmortem findings of Synthetic cowdung powder (sani powder) poisoning in Western Tamil Nadu i.e, Coimbatore, the Nilgiris, Tiruppur, Erodeand Karur districts, the study being conducted in the Department of Forensic Medicine, Coimbatore MedicalCollege.The following parameters were collected and analyzed: the deceased’s sex and age, Post mortem findings,histopathological and chemical analysis reports.A total number of 224 cases were analyzed. Most of the deceasedpersons are of age between 31 to 40years in females (38.8%) andbetween 41 to 50years in males (36.6%). Most ofthe deceased persons were males(78.1%). Postmortem findings of yellow cow dung poisoning were yellowishdiscoloration of skin. Internal findings noted were tongue yellow coated. All the internal organs were stainedyellow.Intense Vigil and Strict Enforcement of regulations for manufacturing and selling of synthetic dyes cansignificantly reduce the incidence of Synthetic Yellow Cow Dung(Saani) powder poisoning.
Keywords: Yellow cow dung, Auromine, Synthetic dye, Saani powder